The Two-Wheeled Workhorse: The Bicycle as Personal and Commercial Transport in Winnipeg - Lehr, John; Selwood, H. John (Urban History Review / Revue d'histoire urbaine, 1999)
The bicycle has yet to be afforded its rightful place in Canadian urban transportation history. Previous interest in the bicycle has centred on the gay nineties cycling craze, when the bicycle was a relatively expensive plaything of the wealthy, leisured classes. This paper outlines that short phase in the history of the bicycle in Winnipeg but focuses on its later utilitarian function as a personal conveyance, giving mobility and freedom to the less affluent but far more numerous working classes. Despite Winnipeg's harsh winter climate, it served not only as a summertime recreational form of transport but also as a year-round workhorse and commuting vehicle.